Effects of drought and their mitigation strategies in Yobe State, Nigeria - Abdullahi Hassan Gana; M. A. Fullen; D. Oloke (Sustinere: Journal of Environment and Sustainability, 2021)
Drought is regarded as a natural phenomenon and its impacts accumulate slowly over a long period. It is considered to be insufficient precipitation that leads to water scarcity, as triggered by meteorological parameters, such as temperature, precipitation and humidity. However, drought mitigation has mostly been reactive, but this has been challenged by extreme events globally. Many countries and regions around the world have made efforts in mitigating drought impacts, including Nigeria. This study produced frameworks for drought amelioration and management as a planning tool for Yobe State, Nigeria. Drought coping strategies have also caused environmental degradation in Yobe State. Farmers over-harvest their farms, practise deforestation and over-exploit wild animals. Several efforts to mitigate the impacts of drought by the Nigerian Government have failed, thus this research adopts a bottom-top approach to mitigate drought impacts in Yobe State. Four validated drought mitigation and management frameworks were developed for Yobe State. The frameworks were evaluated pre-use through respondent validation. State officials and farmers believed that these frameworks will reduce the impacts of drought in Yobe State. The frameworks include social, economic, environmental impact mitigation and an Integrated Drought Mitigation and Management Framework. The proposed frameworks were designed and have advocates a paradigm shift, using both proactive and reactive measures.